The Eroding Standards Issue: A Case Study from the University of Waterloo - Miller, Susan; Goyder, John (Canadian Journal of Higher Education, 2000)
The proposition is addressed that the mathematical skills of first year entrants into the Faculties of Mathematics, Engineering, Science and Applied Health Sciences at The University of Waterloo have declined. Analysis of a series of scores from a mathematics diagnostic test for new students suggests a decline over the period 1991-93 and possibly through to 1995. This reproduces a trend detected at The University of Western Ontario. By the mid-1990s, however, the scores level out. Many of the faculty members questioned in a survey also perceived a decline, and, independently of the time series data, informants pointed to the early 1990s as the critical period of decline. The feeling of being under pressure to adjust to declining standards by upward "belling" of grades varied greatly by faculty, being far more prevalent within the Faculty of Mathematics than in other faculties surveyed. The survey respondents claimed that most deficiencies in mathematics preparation in the high schools were remediable by working to alter the attitudes and expecta- tions of first year university students.